(untitled) (Revista Brasileira Multidisciplinar, 2023)
For a long time, innovation was the result of research carried out in a laboratory environment (R&D), within organizations, which is the Closed Innovation (CI) model. This model was wearing out due to changes in the conditions in which companies innovated and in this context the concept of Open Innovation (OI) emerges as the intentional entry and exit of knowledge across the company’s borders. One of the practices proposed by OI is the acquisition of knowledge from external sources, which help in the innovation processes. Universities occupy a prominent position as agents of innovation, as they are important sources for the generation of new knowledge. Thus, the objective of this work is to evaluate how the professional master’s degree in production engineering from a private educational institution can be considered an external source of knowledge for the OI ​​strategy of some companies. To this end, a study of data from a university in the interior of São Paulo was conducted. Initially, a literature review was carried out on open innovation and a documentary analysis of intellectual production from February 2011 to December, of 156 dissertations from the professional master’s degree in production engineering at the university, object of this study, by analyzing the results of the dissertations, especially those that impacted as gains in new technologies, knowledge, skills for the company, it was possible to identify evidence that the professional master’s degree contributes as an external source of knowledge to the open innovation strategy for companies.